BANTUAN PENJAMINAN KREDIT PERMODALAN TERHADAP USAHA MIKRO KECIL MENENGAH DALAM CORONA VIRUS DISEASE 2019 (COVID-19) - Safari Sidiq Ponco Nugroho (2022)
In 2020 the Indonesian people affected by the Covid-19 pandemic virus resulted in many sectors of the country's economy deteriorating and experiencing a decline, especially traders or entrepreneurs where it was difficult to carry out their business activities. resulting in many closures of business activities ranging from micro, small, and medium enterprises (MSMEs). There are many problems faced by business actors in looking for ways to continue their business activities, one of which is by applying for credit for business capital. The government carries out policy making in handling the economic activities of people affected by Covid-19 by issuing a National Economic Recovery policy which assists business actors, namely (MSMEs) in carrying out their business activities. Based on the explanation above, the author makes a research entitled Capital Credit Guarantee Assistance for Micro, Small and Medium Enterprises where the problem is formulated as Constraints in the Distribution of the Distribution of the National Economic Recovery program and the benefits of distributing the National Economic Election through PMK Number 71/pmk/2020 which was made by the Minister of Finance as distributor of government activities in the face of Covid-19. This research uses normative legal research and empirical legal research. Therefore, the data used include primary data and secondary data. Data were collected using library research and field research using interview methods. To find out more about how Government Policies help Micro, Small and Medium Enterprises.